DESIGN OF WAVE-INDUCED ENERGY CONVERTER LAYOUT AT EAST NUSA TENGGARA - Akbar Putra Bharata, Alif
Indonesia as one of the countries that have a lot of natural resources has a lot of potentials to produce electricity that could be consumed by the entire community, but in reality, some regions in Indonesia still have an electrification ratio of less than 80%. Renewable energy is an alternative to produce electricity. Indonesia already implemented electricity generation with renewable energy, but yet to touch resources from the sea. One of the biggest renewable energy from the sea is wave energy. By matching the wave energy potential map and the electrification ratio map in Indonesia, East Nusa Tenggara has a very high wave energy potential and has a relatively low electrification ratio compared to other regions in Indonesia. East Nusa Tenggara has a relatively high wave height and a relatively long wave period in the southern seas, hence the power plant will be located in the southern seas of East Nusa Tenggara. Sumba Island will be the target of electricity distribution from the plant, an island that has a relatively low electrification ratio compared to other main islands and has a “Sumba Iconic Island“ project, a project to generate 100% electricity in Sumba Island using renewable energy only. The location of the power plant is determined using wave parameter data provided by ECMWF for the past 10 years in the Sumba Island area. The wave energy power plant will be located at 119.191o East Longitude and 9.783o South Lattitude, with a depth of 101.2 meters and 13 kilometers away from the nearest PLN (electricity distribution corporation owned by Indonesia government) network. Pelamis will be the main component of the power plant, a wave generator technology that floats in the water and utilizes the movement of hinges between the sections of the device to produce electricity. One Pelamis instrument can generate 696.639 kWh worth of electricity with a maximum capacity of 79.525 kW. 28 Pelamis will be installed to generate 1.88 MW worth of electricity in Sumba Island. Financial analysis shows the price of electricity per kWh from the power plant is Rp. 7,260 or 2.7 times from the current price in East Nusa Tenggara in 2019.